Substrate stiffness can affect the crosstalk between adipose derived mesenchymal stem cells and macrophages in bone tissue engineering - Liu, Zeyang; Liu, Jin; Li, Jipeng; Li, Yinwei; Sun, Jing; Deng, Yuan; Zhou, Huifang (Frontiers in Bioengineering and Biotechnology, 2023)
Purpose: This study aimed to explore the effect of biomaterials with different stiffness on Adipose Derived Mesenchymal Stem Cells (ADSC)–macrophage crosstalk in bone tissue engineering and its role in bone repair. Methods: Biomaterials with Young's modulus of 64 and 0.2 kPa were selected, and the crosstalk between ADSCs and macrophages was investigated by means of conditioned medium treatment and cell co-culture, respectively. Polymerase chain reaction (PCR) and flow cytometry were used to evaluate the polarization of macrophages. Alkaline phosphatase (ALP) and alizarin red staining (ARS) solutions were used to evaluate the osteogenic differentiation of ADSCs. Transwell assay was used to evaluate the chemotaxis of ADSCs and macrophages. Moreover, mass spectrometry proteomics was used to analyze the secreted protein profile of ADSCs of different substrates and macrophages in different polarization states. Results: On exploring the influence of biomaterials on macrophages from ADSCs on different substrates, we found that CD163 and CD206 expression levels in macrophages were significantly higher in the 64-kPa group than in the 0.2-kPa group in conditioned medium treatment and cell co-culture. Flow cytometry showed that more cells became CD163+ or CD206+ cells in the 64-kPa group under conditioned medium treatment or cell co-culture. The Transwell assay showed that more macrophages migrated to the lower chamber in the 64-kPa group. The proteomic analysis found that ADSCs in the 64-kPa group secreted more immunomodulatory proteins, such as LBP and RBP4, to improve the repair microenvironment. On exploring the influence of biomaterials on ADSCs from macrophages in different polarization states, we found that ALP and ARS levels in ADSCs were significantly higher in the M2 group than in the other three groups (NC, M0, and M1 groups) in both conditioned medium treatment and cell co-culture. The Transwell assay showed that more ADSCs migrated to the lower chamber in the M2 group. The proteomic analysis found that M2 macrophages secreted more extracellular remodeling proteins, such as LRP1, to promote bone repair. Conclusions: In bone tissue engineering, the stiffness of repair biomaterials can affect the crosstalk between ADSCs and macrophages, thereby regulating local repair immunity and affecting bone repair.